(3JaSjQ GdTQjYIs - (3Uaj GdOjf, GHf CHj GdQLGd, CMeO Hf UGdM Hf CHj GdQLGd, J (B1092(3g`s ((3HNW eDdagGs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3GYde CjgG GdfGXQ dfaSg Efc aj gPG GdhLhO(B...(3hCYOGDc dG JbHd efc GdaOGA(B...s
(3BNQgG (B:s
(3adG Tc Cfg Chge Cf CFeI GdYJQI ZjQ YOhd hdG KbGJ ajeG GNJUhG Hg ef GdQhGjI hYdehg ef GdQhGjI(B...s
(3aj BNQg eWGdYI HJGQjN (B28 (3QeVGf (B1148(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B137s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds